2016
DOI: 10.1073/pnas.1523064113
|View full text |Cite
|
Sign up to set email alerts
|

Concealed d -wave pairs in the s ± condensate of iron-based superconductors

Abstract: A central question in iron-based superconductivity is the mechanism by which the paired electrons minimize their strong mutual Coulomb repulsion. In most unconventional superconductors, Coulomb repulsion is minimized through the formation of higher angular momentum Cooper pairs, with Fermi surface nodes in the pair wavefunction. The apparent absence of such nodes in the iron-based superconductors has led to a belief they form an s-wave (s ± ) singlet state, which changes sign between the electron and hole pock… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…The pairing of electrons with additional internal degrees of freedom resulting, e.g., from different orbitals or basis sites, can lead to qualitatively new pairing states. Such pairing states have for example been proposed for iron-based superconductors [2][3][4][5][6][7][8][9], Cu x Bi 2 Se 3 [10,11], cubic systems such as half-Heusler compounds [12][13][14][15][16][17][18][19][20][21], UPt 3 [22,23], transition-metal dichalcogenides [24,25], and twisted bilayer graphene [26][27][28]. It has been shown that in centrosymmetric multiband superconductors that break TRS, point and line nodes are generically "inflated," by interband pairing, into Fermi surfaces of Bogoliubov quasiparticles [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The pairing of electrons with additional internal degrees of freedom resulting, e.g., from different orbitals or basis sites, can lead to qualitatively new pairing states. Such pairing states have for example been proposed for iron-based superconductors [2][3][4][5][6][7][8][9], Cu x Bi 2 Se 3 [10,11], cubic systems such as half-Heusler compounds [12][13][14][15][16][17][18][19][20][21], UPt 3 [22,23], transition-metal dichalcogenides [24,25], and twisted bilayer graphene [26][27][28]. It has been shown that in centrosymmetric multiband superconductors that break TRS, point and line nodes are generically "inflated," by interband pairing, into Fermi surfaces of Bogoliubov quasiparticles [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…22,23,28 Such orbital selectivity has also been the subject of extensive recent theoretical studies. [29][30][31] All these aspects make it natural to study orbital-dependent [32][33][34] and -related 35 superconducting pairing. We are thus motivated to address the hitherto unexplored question, viz.…”
Section: Resultsmentioning
confidence: 99%
“…This picture has recently been challenged for a number of materials. For iron-based superconductors, the role of interorbital pairing is attracting increased attention [3][4][5][6]. Another example is the nematic superconductivity of Cu x Bi 2 Se 3 [7], where the odd parity of the gap is encoded in the orbital degrees of freedom.…”
mentioning
confidence: 99%